The Influence of Digital Literacy And The Utilization of Online Learning Media on The Competence of Elementary School Teachers - Yohana, Yohana; Suroyo, Suroyo; Sukmayadi, Dodi (International Journal of Law Policy and Governance, 2025)
This research is a quantitative study that aims to determine the effect of teacher digital literacy on the utilization of online learning media and the competence of elementary school teachers in Bongan District, West Kutai Regency. Sampling using random sampling technique. Data collection was done with a closed question questionnaire with a Likert scale. The collected data were analyzed by multiple linear regression. The study found that partially there is no significant effect of digital literacy on teacher competence and produced a regression equation Y = 109.989 + 0.209X1 + 0.05.. Meanwhile, the utilization of online learning media has a significant effect on teacher competence and produces a regression equation Y = 95.005 + 0.281X2 + 0.05. Multiple regression analysis found that digital literacy and utilization of online learning media simultaneously have a significant effect on teacher competence. the test results of the coefficient of determination (R Square) produced an R square number (0.218) has a meaning equal to 21.8%. This figure means that the variance of the teacher competency variable (Y) contributed a value of 21.8%. Then the remaining 78.2% (100% - 21.8% = 78.2%) is influenced by other variables not examined in this study.